Mechanistic insight to ROS and Apoptosis regulated cytotoxicity inferred by Green synthesized CuO nanoparticles from Calotropis gigantea to Embryonic Zebrafish. Issue 1 (December 2017) - Kumari, Puja; Panda, Pritam; Jha, Ealisha; Kumari, Khushboo; Nisha, Kumari; Mallick, M.; Verma, Suresh
Abstract With the rapid development of nanotechnology, much has been anticipated with copper oxide nanoparticles (CuO NP) due to their extensive industrial and commercial application. However, it has raised concern over the environmental safety and human health effects. In this study, CuO nanoparticles were synthesized using the green method with floral extract ofCalotropis gigantea and characterized by standard physiochemical techniques like DLS, Zeta potential determination, UV- Visible Spectroscopy, XRD, FTIR, FESEM, and TEM. Mechanistic cytotoxicity studies were performed using experimental and computational assays including morphological analysis, hatching, and viability rate analysis along with ROS and apoptosis analysis. Physiochemical characterization of CuO NP determined the size and zeta potential of synthesized nanoparticles to be 30 ± 09 nm to 40 ± 2 nm and −38 mV ± 12 mV respectively. Cytotoxicity evaluation with Zebrafish revealed malfunctioned organ development with differential viability and hatching rate at 48 hpf and 72 hpf with LC50 of 175 ± 10 mg/l. Computational analysis depicted the influential role of CuO nanoparticles on zebrafish embryo's he1a, sod1 and p53 functional expression through hydrophobic and hydrogen bond interaction with amino acid residues. Study demonstrated valuable information of cytotoxic impact which can be influential in further studies of their eco-toxicological effects.